Rectified electron transfer across fullerene multilayers on ITO surface - Oh, SY; Han, SH (ELSEVIER SCIENCE SA, 2001)
Stacks of fullerene layers were constructed on the ITO surface. The cyclic voltammetry and chronopotentiometry showed that the diffusion of Fe(CN)(6)(-3) to the ITO surface is inhibited in the presence of the fullerene layers, and that electrons are transferred across the fullerene films. Unidirectional electron transfer was observed, indicating a rectifying character of the fullerene-modified ITO electrodes.